Stable carbon isotope ratios of n-alkane from peat core IMB100, Imbonga, Democratic Republic of Congo - Johanna Menges; David Sebag; Judicael Lebamba; Christopher Albert Kiahtipes; Johannes Preuß; Ferdinand Bokomba Bwamangele; Roger Kidebua Lutonadio; Melanie Guardiola; Thierry Adatte; Yannick Stroobandt; Steven Bouillon; Yannick Garcin; et al. (PANGAEA, 2025)
This data publication contains an organic geochemistry dataset from the IMB100 peat core, recoverd from a river proximal peatland in the Cuvette Centrale, Democratic Republic of Congo. The dataset was generated to investigate Holocene peat formation and hydroclimatic conditions within the Cuvette Centrale during this time period. The Imbonga (IMB100) peat core was recovered from peatlands in the Ingende Territory (Équateur Province) in the Democratic Republic of Congo during a fieldtrip in March 2017. The coring site of the IMB100 core (0.856693°S and 19.808078°E, elevation: 320 m.a.s.l.) is located at the northern edge of a small basin filled with peat, around 800 m distance from the Momboyo River, a tributary of the Ruki River that joins the Congo main stem at Mbandaka. The peat core was collected within the Raphia hookeri peatland forest using a hand operated 60 mm diameter Eijkelkamp gouge auger. Archived data on the peat core consists of radiocarbon ages on the fine fraction and macro remains, bulk organic carbon and nitrogen concentrations and stable isotopes, Rock-Eval® derived parameters, and plant wax carbon and hydrogen isotope compositions.